Reflection of the effect of empowering leadership behaviors on the workforce agility (An analytical study of the opinions of teachers in the private schools of the Diwaniyah governorate center) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aimed to test the effect of empowering leadership behaviors expressed with itsdimensions (leadership by example, participatory decision-making, training, information exchange,showing interest with others) on workforce agility (flexibility, adaptation ,proactivity) in privateschools in Al-Diwaniyah Governorate,and the problem was summarized with a set of questionsbased on the researcher’s perceptions, the most important of which resulted in the statement of theinfluence that empowering leadership behaviors exert on workforce agility, and for achieve theobjectives of the study, a hypothetical scheme was designed that embodies the nature of therelationship between the variables included in the study, and a set of hypotheses were built aimed atidentifying The level of the relationship between empowering leadership behaviors and workforceagility in private schools in Al-Diwaniyah Governorate, and the study relied on the nature of thequestionnaire as a main tool in collecting data and information from a sample of (273) facultymembers, and the study used a set of statistical programs represented in (SPSS). V.26 &AMOS.V.26) in order to reach the results that the study aspires to answer, using several statisticalmethods, especially in (the arithmetic mean, standard deviation, relative importance, coefficient ofvariation, t-test, simple correlation coefficient, and the structural equation modeling(.